Порошенко А. І. Філософія холізму та можливості використання її положень у сучасних системах аудіо аналітики - Порошенко, А. І. (ХНУРЕ, 2022)
This paper is concerned with possibilities of using the concept sof the philosophy of holism in modern systems of audio analytics. There is a need to consider the meaningful and meaningless parts of the audio signal in their entirety. The meaningful part is the audio signal itself, and the meaningless part is its interpretation in the global context of audio events. This theory requires the creation of an additional dictionary for the analysis of the meaningless part of the audio signal that consist of the previous and subsequent audio signals based on the study of existing data sets. Such system requires a complex stage of machine learning but will significantly improve the accuracy of audio signals recognition using the context
Keywords: аудіо аналітика